The field description of igneous rocks - Jerram, Dougal; Petford, Nick (Nicholas) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"The second edition of this unique pocket field guide has been thoroughly revised and updated to include the advances in physical volcanology, emplacement of magmas, and interpreting structures and textures in igneous rocks. The book has included new techniques, such as AMS and geophysical studies of pluton shape at depth, and new topics such as the occurrence of porphyrys, laccoliths, and magma sediment interaction. Part of the successful field guide series, this book includes new sections featuring granitic rocks, basaltic rocks, magma mixing and mingling, and engineering properties and mineralization."--
"The second edition of this unique pocket field guide has been thoroughly revised and updated to include the advances in physical volcanology, emplacement of magmas and interpreting structures and textures in igneous rocks"--
Rev. ed. of: The field description of igneous rocks / R.S. Thorpe and G.C. Brown. Milton. Keynes [Buckinghamshire] : Open University Press ; New York : Halsted, 1985.
Includes bibliographical references (p. 231) and index.
Keywords: Igneous rocks -- Identification; Geology -- Fieldwork